Interruption of anticoagulation in patients undergoing elective surgical procedures - Łętek, Agnieszka; Zandecki, Łukasz; Janion-Sadowska, Agnieszka; Polewczyk, Anna (Medical Studies/Studia Medyczne, 2020)
Interruption of long-term therapy with oral anticoagulants in patients undergoing elective surgical procedures is a common problem in clinical practice. A large number of patients are receiving oral anticoagulants due to atrial fibrillation, mechanical prosthetic valves, or thromboembolic disease. Each year many of these patients will undergo an invasive procedure. The most important aspect is the risk-benefit assessment: the general risk of bleeding related to the procedure, additional risk of bleeding during the procedure related to anticoagulants, and on the other hand the risk of thrombotic complications such as ischaemic stroke or coronary stent thrombosis, associated with discontinuation of the antithrombotic therapy. The aim of the article is to present the management of anticoagulant therapy in patients undergoing elective surgical procedures.